Hubungan Parental Phubbing Dengan Problematic Internet Use Pada Remaja Di Sumatera Barat - Febrilla, Rafika (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
The use of the internet has many benefits and also makes it easier for someone to do their work, in addition to the positive benefits, if it is used inappropriately it will trigger problems such as problematic internet use. Problematic internet use according to Demetrovis et al, (2008) is a condition where someone has difficulty controlling internet use. One of the factors causing problematic internet use is parental phubbing. The purpose of this study was to analyze the relationship between parental phubbing and problematic internet use in adolescents in West Sumatra with 400 respondents selected using cluster sampling techniques from five randomly determined districts/cities. This research instrument was independently compiled by the researcher based on the theory put forward by Demetrovis et al, (2008) to measure problematic internet use, and Pancaniet al,(2021) to measure parental phubbing behavior. Based on the results of the Pearson product moment correlation test, the correlation value was obtained r = 0.192 and p = 0.00 (p <0.05) which indicates that there is a positive relationship between parental phubbing in parents and problematic internet use in adolescents in West Sumatra.